The effects of short-term isometric training program on the neuromuscular function of elite Greek jumpers and long distance runners - Patikas, D.; Paraschos, I.; Bassa, E.; Galazoulas, C.; Skoufas, D.; Kotzamanidis, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The improvement of performance in track and field sports requires specific training, depending on the features of the event. Rate of force development (RFD) is crucial for jumpers, whereas long distance runners` RFD is expected as less developed. Short-term effects of training may influence performance. However, it is still unknown how such athletes respond to a short-term training protocol. The aim of the present study was to examine the effect of a two days strength training protocol on the neuromuscular function and especially on the RFD of the plantar flexor muscles in elite jumpers and long distance runners. Methods: Two groups of elite Greek track field jumpers (n=9, age: 24.8±3.1 years, height: 182.3±7.4 cm, body mass: 74.3±2.7 kg) and long distance runners (n=9, age: 22.1±2.8 years, height: 177.9±6.7 cm, body mass: 64.8±7.3 kg) participated in the study. The participants were tested 48 h before and after an isometric, ballistic type, strength training protocol consisted of 2 sessions with 48 hours interval in between. Testing and training were conducted on the plantar flexor muscles of the ankle. Torque and EMG amplitude as well as frequency component using spike analysis for the gastrocnemius, soleus and tibialis anterior were measured during the maximal voluntary contraction. Additionally, the maximal M-wave (Mmax) and the twitch torque properties were measured after a supramaximal electrical nerve stimulation over the tibial nerve. Results: Maximal voluntary isometric torque remained unchanged, while, the voluntary maximal RFD recorded 100 ms after the onset of contraction improved in the long distance runners only. This was accompanied by an increase in the gastrocnemius EMG frequency as well. The peak twitch torque, contraction time, half relaxation time and Mmax remained unchanged in both groups. However, before training jumpers presented higher twitch torque, shorter contraction time and shorter half relaxation time, compared to the values of the long distance runners. Discussion: Our findings indicate that RFD is enhanced after 2 sessions of strength training program, with no parallel increase in maximal strength, only in persons with low level of strength (Blazevitz et al., 2008). Considering the examined muscles, it seems that such adaptations are evident in muscles with larger proportion of fast motor units, such as gastrocnemius (Paasuke et al., 1999). This supports the notion that spinal and supraspinal centers may contribute to the adaptations observed after a short-term, ballistic, isometric training.